Untersuchungen zur Morphologie der Gelenksinnesfelder der Wiesenameise Formica pratensis Retzius, 1783 (Hymenoptera: Formicidae). - Fröhlich, Christine (Contributions to Entomology = Beiträge zur Entomologie, 1969)
Previous work and recently published studies induced the author to examine macroscopically and microscopically the sensory organs at the joints of Formica pratensis Retzius, 1783. The results are described with special regard to the structures at the "neck joint".